The effect of a proposed educational program using specific exercises to develop motor response, motor satisfaction, and short-term defensive movement skills in handball (Global Scientific Review, 2024)
This research aims to evaluate the effectiveness of a specific educational program in improving the motor performance of handball players by measuring its effect on motor response speed, increasing motor satisfaction, and improving limited defensive movement skills. The experimental method was used, and the players of the AlTaawon Sports Club junior category represented the research sample. The researchers used the motor response speed test to measure the motor response time with a visual stimulus, the motor satisfaction scale to identify the degree of individual satisfaction with his movements and motor and physical characteristics, and the short-term defensive movements test to measure the player's speed in short-term defensive movements. After conducting the pre-tests and implementing the educational program, then conducting the post-tests, the data were recorded and organized in specific tables to obtain the test results using the following statistical methods: the arithmetic mean, the standard deviation, and the calculated (t) value. The calculated t-values showed statistically significant differences (p